"A manageable and challenging fall prevention intervention with impact on society" - older women's perspectives on participation in the stayBalanced training programme. (18th November 2022) - Halén, Carolina; Gripenberg, Susanne; Roaldsen, Kirsti Skavberg; Dohrn, Ing-Mari; Halvarsson, Alexandra
ABSTRACT: Introduction: Efficient and effective evidence-based practice (EBP) strategies for managing fall prevention in primary health care are of great importance. To ensure that EBP methods have the potential to be implemented and maintained in clinical practice, patient perspective must be ensured. Novel programs need to be perceived as meaningful and feasible, and in line with the patients' values, preferences and needs. Purpose: To describe how older women with osteoporosis experience participation in the StayBalanced Programme. Methods: Individual semi-structured interviews with 39 women aged 67–86 with osteoporosis, impaired balance and fear of falling. Data were analyzed with thematic analysis. Results: The analysis resulted in three main themes; "Managing and challenging training through support and enjoyment, " "Structured training leads to safety and self-awareness" and "Lack of structured balance training means missed benefits, for both the individual and society." The participants experienced that the increased safety and self-awareness achieved through the challenging and motivating training, were transferred to daily life, thus, leaving them less exposed to falls, fall injuries and fear of falling. They expressed concerns about lack of knowledge translation regarding the positive effects of structured and challenging balance training, which left older adults and society without the benefits of evidence-based intervention. Conclusions: The StayBalanced Programme was appreciated and acceptable from the perspective of the participants, and in line with their values and preferences, one of three key components of EPB. The results of this study may support the uptake of the evidence-based StayBalanced Programme for fall prevention in clinical practice.